Analisis Struktur Bawah Permukaan Tanah Menggunakan Metode Geolistrik 3D Studi Kasus: Area Kampus Universitas Pertahanan Republik Indonesia, IPSC, Bogor - Wafi, Abdurrahman; Fansuri, Muhammad Hamzah (Jurnal Inovasi Konstruksi, 2024)
Subsurface conditions are very important as a basis for infrastructure development so that the right actions can be taken. One method to determine subsurface conditions is the geophysical method, namely the geoelectric method. The geoelectric method is a geophysical method that utilizes the resistivity value of the material. The purpose of this study is to obtain a 3D model of subsurface conditions based on their resistivity values. Data collection uses MAE X612-EM geoelectric equipment and processing uses ERTLab software. The area studied is 70m long with 10m wide, the depth obtained is 11.6m. The 3D section results show a resistivity value of 2.96 Ωm – 9 Ωm from the model obtained. The surface is dominated by hard material marked in red on the 3D model. A zone with a low resistivity value distribution of 2.96 Ωm was obtained in the middle at a distance of 17 -40m at adepth of 5.56m which is suspected to be a water trap. In the 3D model, it is assumed to get 3 layers, which are marked in red. green and blue which represent the respective resistivity values. Keywords: Resistivity, geoelectric,water,subsurfaces